TAHAPAN PERKARA PERDATA UNTUK TINGKAT KASASI - Yuliska, Edwin (Fakultas Hukum Universitas Tamansiswa Padang, 2021)
The maximum period for handling cases according to the internal provisions of the Supreme Court, from the submission of the appeal to the district court until the delivery of a copy of the decision to the district court is 315 days. However, in practice, the handling of cassation cases can take longer than the time period that has been set by the Supreme Court itself. In addition, the Parties can monitor the status of the settlement of their cases through the case info page on the Supreme Court Registrar's website or the SIPP website of the district court at the place of filing the initial case or If the Parties find that the time period for handling cases exceeds the time period set by the Supreme Court, they can directly ask the Registrar of the Supreme Court either through letter or go directly to the information desk at the MA.